Gender Inclusion in an Indian VUCA World. Issue 2 (April 2019) - Rajesh, Saundarya; Ekambaram, Karthik; Rakesh, Anju; Kumar, Divya
Abstract: One of the most crucial talent identity strands (also referred to as a human resources dimension) in India Inc. is gender. Given that the rate of change in a volatile, uncertain, complex and ambiguous (VUCA) environment is much faster (and less predictable) than in the past decades, corporate efforts towards managing this dimension of gender have a strong bearing on their ability to effectively combat VUCA. These efforts include those directed towards talent management—attracting, hiring, retaining and developing talent, catering to the differences in aspirations and working styles of men and women. Against this backdrop, this article draws insights from corporate India's most comprehensive gender analytics exercise—The Working Mother and AVTAR 100 Best Companies for Women in India study—to shed light on the interlinkage between the intent and commitment in employing diversity and inclusion as a culture strategy towards thriving in a VUCA environment.